Supporting Educational Success for Aboriginal Students: Identifying key influences - Whitley, Jessica (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2014)
The academic difficulties experienced by many Aboriginal (First Nations, Métis, Inuit) students in Canada have been well-documented. Indicators such as school persistence and post-secondary enrollment are typically far lower for Aboriginal students as a group compared to non-Aboriginal students. Identifying facilitators of success is key to improving the academic experiences of Aboriginal students. Accordingly, the objective of the current study was to identify influential factors related to the educational success of Aboriginal students, from the perspective of students and teachers, through the lens of Bronfenbrenner’s (1995) “Bioecological Model.” The insights of participants spoke to the importance of relationships, self-concept and academic expectations, the relevance of the school curriculum, and academic aspirations as factors influencing educational success.